Comparison of intravenous and subcutaneous exposure supporting dose selection of subcutaneous belimumab systemic lupus erythematosus Phase 3 program. (November 2016) - Yapa, S Wickramaratne Senarath; Roth, D; Gordon, D; Struemper, H
Background: Belimumab is a recombinant, human, IgG1λ monoclonal antibody that targets B-lymphocyte stimulator. The intravenous formulation is indicated for the treatment of active, autoantibody-positive systemic lupus erythematosus (SLE). Belimumab has been formulated for subcutaneous (SC) administration to improve patient convenience. This post-hoc modeling and simulation analysis characterizes the population pharmacokinetics (PK) of SC belimumab, and compares the exposure profiles of the approved belimumab IV dose—10 mg/kg every four weeks—to the 200 mg SC weekly dose in SLE patients, highlighting key pharmacological differences relevant for clinicians. Methods: Data from two Phase 1 studies in US American and Japanese healthy subjects were analyzed with a non-linear mixed effects modeling approach. The resulting SC population PK model and a previously developed IV population PK model were used to conduct simulation trials in a Phase 3 IV belimumab SLE patient population, comparing chronic exposure profiles and exposure ranges stratified by body weight tertiles for IV vs SC dosing. Results: The PK of belimumab following SC administration was best described by a linear two-comment model. The estimates for clearance, steady-state volume of distribution, and bioavailability were 208 mL/day, 5250 mL, and 76%, respectively. After four weeks of SC dosing, simulated belimumab concentrations exceeded the steady-state trough concentrations of the IV dosing regimen. At steady state simulated serum profiles demonstrated comparable average belimumab concentrations (Cavg, ss ) after IV and SC dosing. Simulated belimumab exposures demonstrated largely overlapping concentration ranges following 200 mg SC weekly and 10 mg/kg IV every four weeks dosing. Discussion: The predicted Cavg, ss of belimumab in SLE patients was comparable following 200 mg SC weekly and 10 mg/kg IV every four weeks dosing. The simulated belimumab accumulation following SC weekly dosing indicated that administration of a loading dose was not required. Similar Cavg, ss ranges were predicted for fixed dose SC and weight-proportional IV regimens in the simulated SLE population, albeit with a reversed body-size-to-exposure relationship for the SC regimen. These findings provide rheumatologists with a better understanding of expected differences in belimumab exposure when comparing IV and SC dosing regimens.